Unemployment, public-sector healthcare spending and stomach cancer mortality in the European Union, 1981-2009. - Maruthappu, M; Painter, A; Watkins, J; Williams, C; Ali, R; Zeltner, T; Faiz, O; Sheth, H (Lippincott Williams and Wilkins, 2014)
OBJECTIVES: We sought to determine the association between changes in unemployment, healthcare spending and stomach cancer mortality. METHODS: Multivariate regression analysis was used to assess how changes in unemployment and public-sector expenditure on healthcare (PSEH) varied with stomach cancer mortality in 25 member states of the European Union from 1981 to 2009. Country-specific differences in healthcare infrastructure and demographics were controlled for 1- to 5-year time-lag analyses and robustness checks were carried out. RESULTS: A 1% increase in unemployment was associated with a significant increase in stomach cancer mortality in both men and women [men: coefficient (R)=0.1080, 95% confidence interval (CI)=0.0470-0.1690, P=0.0006; women: R=0.0488, 95% CI=0.0168-0.0809, P=0.0029]. A 1% increase in PSEH was associated with a significant decrease in stomach cancer mortality (men: R=-0.0009, 95% CI=-0.0013 to -0.005, P<0.0001; women: R=-0.0004, 95% CI=-0.0007 to -0.0001, P=0.0054). The associations remained when economic factors, urbanization, nutrition and alcohol intake were controlled for, but not when healthcare resources were controlled for. Time-lag analysis showed that the largest changes in mortality occurred 3-4 years after any changes in either unemployment or PSEH. CONCLUSION: Increases in unemployment are associated with a significant increase in stomach cancer mortality. Stomach cancer mortality is also affected by public-sector healthcare spending. Initiatives that bolster employment and maintain public-sector healthcare expenditure may help to minimize increases in stomach cancer mortality during economic downturns.